Fourier-Transform Raman and Fourier-Transform Infrared Spectroscopy (An Investigation of Five Higher Plant Cell Walls and Their Components). - Sene, CFB. (1994)
Infrared and Raman spectra of sequentially extracted primary cell walls and their pectic polymers were obtained from five angiosperm plants. Fourier-transform Raman spectrometry was shown to be a powerful tool for the investigation of primary cell-wall architecture at a molecular level, providing complementary information to that obtained by Fourier-transform infrared microspectroscopy. The use of an extraction procedure using imidazole instead of cyclohexane trans-1,2-N,N,N[prime],N[prime]-diaminotetraacetate allows the extension of the infrared spectral window for data interpretation from 1300 to 800 cm-1, to 2000 to 800 cm-1, and allows us to obtain Raman spectra from extracted cell-wall material. Wall constituents such as pectins, proteins, aromatic phenolics, cellulose, and hemicellulose have characteristic spectral features that can be used to identify and/or fingerprint these polymers without, in most cases, the need for any physical separation. The Gramineae (rice [Oryza sativa], polypogon [Polypogon fugax steud], and sweet corn [Zea mays]) are spectroscopically very different from the nongraminaceous monocotyledon (onion [Allium cepa]) and the dicotyledon (carrot [Daucus carota]); this reflects differences in chemical composition and cross-linking of the walls. The possibility of a taxonomic classification of plant cell walls based on infrared and Raman spectroscopies and the use of spectral fingerprinting for authentication and detection of adulteration of products rich in cell-wall materials are discussed.